Determinan Harga Saham Perusahaan Sub Sektor Hotel, Resort & Cruises Lines Yang Terdaftar Indeks Saham Syariah Indonesia - Roosyidah, Naafi'atul; Dwiputri, Inayati Nuraini; Prasetiyani, Erni (Perbanas Journal of Islamic Economics and Business, 2025)
Stock price is an important indicator to describe the potential profit of investment and also reflects the company's performance in the eyes of investors. Therefore, it is important for companies to maintain good financial performance so that stock prices remain stable or increase. Although there have been many studies discussing the factors that affect stock prices, there are still few studies conducted specifically on sharia-based companies in the Hotel, Resort, and Cruise Line sub-sector in Indonesia. In addition, there are still few studies that combine internal factors (such as profitability and capital structure) and external factors (such as the Covid-19 pandemic) in one analysis simultaneously. This study aims to examine the effect of profitability (as measured by Earning Per Share (EPS), Price to Earning Ratio (PER), and Net Profit Margin (NPM)), capital structure (as measured by Debt to Assets Ratio (DAR)), and external conditions (as represented by the Covid-19 dummy variable) on the stock prices of companies in the Hotel, Resort, and Cruise Lines sub-sector listed on the Indonesian Sharia Stock Index (ISSI). The data used are secondary data from company financial reports and publications of the Indonesia Stock Exchange (IDX) for the period 2017–2023. The population in this study consisted of 19 companies, with a sample of 14 companies selected using purposive sampling techniques. The analysis method used is multiple panel data regression. The results of the study show that EPS and PER have a positive effect on stock prices, while DAR has a negative effect on stock prices. NPM and the Covid-19 dummy have no effect on stock prices. Based on these findings, companies are advised to increase profitability and manage capital structure well in order to maintain investor confidence and support positive stock price movements